Pertussis over two decades: seroepidemiological study in a large population of the Siena Province, Tuscany Region, Central Italy - Serena Marchi; Emanuele Montomoli; Edmond J Remarque; Geraldo Tadinho Monteverde Spencer; Angela Azzarello; Simonetta Viviani; Claudia Maria Trombetta (BMJ Open)
Objectives To evaluate seroprevalence against Bordetella pertussis in Tuscany, a large Italian region, from 1992 to 2005 and from 2013 to 2016.Design Seroepidemiological study.Participants 1812 serum samples collected in Tuscany from subjects older than 12 years from 1992 to 2005 and from 2013 to 2016.Outcome measures Specific antibody levels were determined by means of standard commercial ELISA using a dual cut-off of 50 and 125 IU/mL as markers of past and recent infection/vaccination, respectively.Results The highest values of IgG titres were observed in 1992–1994 in all subjects (69.5 IU/mL), with prevalence values of subjects with IgG titres of >50 and >125 IU/mL of 68.3% and 23.8%, respectively. IgG titres decreased in the years thereafter (37.8 IU/mL in 2002–2005), together with prevalence values (41.7% and 8.1% in 2002–2005). In 2013–2016, both IgG titres and prevalence values showed a slight increase (50.6 IU/mL, 53.9% and 14.7%, respectively). IgG titres and prevalence followed the same age-related trend in all time periods considered, with the highest values in subjects aged 12–22 years. The lowest values were found in the age group of subjects aged 23–35 years (OR 0.54).Conclusions Since 2002, approximately half of the population over 22 years of age have low IgG titres and are presumably susceptible to acquiring and transmitting pertussis infection. In addition, in 2013–2016, almost one-third of subjects aged 12–22 years, that is, the age group most likely to have been vaccinated against pertussis in infancy, had low antibody levels. Improving vaccination coverage and implementing careful surveillance are therefore recommended in order to prevent morbidity and mortality due to pertussis.